2021
DOI: 10.1029/2021jb022094
|View full text |Cite
|
Sign up to set email alerts
|

Shallow Magma Storage Beneath Mt. Etna: Evidence From New Attenuation Tomography and Existing Velocity Models

Abstract: Determining the location and size of potential magma reservoirs is crucial to constrain the size of future eruptions or eruptive frequency. Magma accumulation and melt migration have been the focus of extensive research at Mt. Etna volcano. Recent geophysical imaging of Mt. Etna has shown the growing importance of several geological bodies in explaining the migration of eruptive materials inside the volcano. One such body, known as the High Velocity Body (HVB), is a highly consolidated structure located below … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 74 publications
(164 reference statements)
1
7
0
Order By: Relevance
“…Etna volcano region. For these studies, two methodologies have been used: 1) the separation of the intrinsic attenuation (Qi −1 ) and scattering (Qs −1 ) contributions through the diffusion model (Wu, 1985) and its 2-D spatial representation (Ibáñez et al, 2020); and 2) a 3-D attenuation tomographic study (Castro-Melgar et al, 2021) using the coda normalization method (Aki, 1980). Therefore, we tested the resolution of both of these methods in this study.…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…Etna volcano region. For these studies, two methodologies have been used: 1) the separation of the intrinsic attenuation (Qi −1 ) and scattering (Qs −1 ) contributions through the diffusion model (Wu, 1985) and its 2-D spatial representation (Ibáñez et al, 2020); and 2) a 3-D attenuation tomographic study (Castro-Melgar et al, 2021) using the coda normalization method (Aki, 1980). Therefore, we tested the resolution of both of these methods in this study.…”
Section: Methodsmentioning
confidence: 99%
“…Only shots generated with the maximum energy presented sufficient quality (based on the signal-to-noise ratio) to be used in tomographic structural models (both velocity and attenuation). Castro-Melgar et al (2021) found that the most energetic shots had an equivalent duration magnitude of up to 1.4, based on the magnitude scale of Havskov et al (2003) for volcanic regions. To this limitation we add a high content of background noise, which is typical of seismic signals in populated areas or on small islands (due to oceanic noise); as such, not all of the signals generated in the experiment were useful for this study.…”
Section: Seismic Datamentioning
confidence: 99%
See 3 more Smart Citations